The Influence of the Role of Halal Tourist Destinations on Interest in Visiting - Putu Nina Madiawati; Sulistijono Sulistijono; Jella Zumalia Fitri (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study was to determine how big the role of the image of halal tourist destinations on visiting interest is influenced by market potential, electronic word of mouth (E-WOM), and social media. The research method uses quantitative methods, with data processing using SEM-PLS (Partial Least Square). The results showed that the role of halal tourist destinations on visiting interest has a big influence. The image of halal tourist destinations will not develop properly if it is not supported by E-WOM, social media, and market potential, which are carried out continuously. Therefore, good cooperation between the local government, the community and all related parties are required to increase halal tourism.